Microwave and RF Design Modules - Steer, Michael (Open textbook library., 2019)
Microwave and RF Design: Modules focuses on the design of systems based on microwave modules. The use of modules has become increasingly important in RF and microwave engineering for rapidly realizing high performance microwave systems. When integration is ultimately to be used, building a system up using modules provides a rapid means of prototyping and testing system concepts. A wide variety of RF modules including amplifiers, local oscillators, switches, circulators, isolators, phase detectors, frequency multipliers and dividers, phase-locked loops, and direct digital synthesizers are considered. Detailed design strategies for synthesizing filters based on parallel coupled lines are presented. The reader will gain an appreciation of design by synthesis. This book is suitable as both an undergraduate and graduate textbook, as well as a career-long reference book.